Die Rolle der131J-Metajod-benzylguanidin-(MIBG-) Szintigraphie in der Diagnostik der intestinalen Karzinoide - Bihl, H.; Sautter-Bihl, M. L.; Wilhelm, K. R.; Kimmig, B. (Nuklearmedizin - NuclearMedicine, 1987)
lodine-131 metaiodobenzylguanidine (131I-MIBG) is concentrated in a variety of neuroendocrine tumors, such as pheochromocytoma and neuroblastoma. Other neuroendocrine tumors from the APUD-cell system such as carcinoid tumors, may posses this uptake capability as well. We investigated 11 patients suffering from intestinal carcinoid with 131I-MIBG in order to determine the value of MIBG scintigraphy in these tumors. MIBG scans were positive in 5 out of 11 patients (45%). False-positive MIBG-scans did not occur. No correlation between MIBG uptake, clinical symptoms and urinary 5-HIAA level could be found.